2014
DOI: 10.1681/asn.2013111149
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Microscope Strategy to Improve Risk Stratification in Early Antibody-Mediated Kidney Allograft Rejection

Abstract: Antibody-mediated rejection (ABMR) is the leading cause of kidney allograft loss. We investigated whether the addition of gene expression measurements to conventional methods could serve as a molecular microscope to identify kidneys with ABMR that are at high risk for failure. We studied 939 consecutive kidney recipients at Necker Hospital (2004-2010; principal cohort) and 321 kidney recipients at Saint Louis Hospital (2006-2010; validation cohort) and assessed patients with ABMR in the first 1 year post-tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
1
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(106 citation statements)
references
References 29 publications
2
96
1
7
Order By: Relevance
“…In addition, when studying the molecular signature of biopsy samples showing ABMR, Sellares et al 14 showed a clear IFNg signature, with CXCL10 being one of the top ABMR classifier genes. 16 In a rat model of acute antibodymediated endothelial injury, among several chemokines and chemokine receptors, CXCL10 was, by far, the most upregulated chemokine (119-fold), a result that also supports our findings. 17 Our multivariate linear regression analysis of the association of Banff scores with urinary biomarker levels revealed that, among microvascular inflammatory lesions, the peritubular capillaritis score but not the glomerulitis score seemed independently and significantly associated with the urinary chemokine level (Table 3).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, when studying the molecular signature of biopsy samples showing ABMR, Sellares et al 14 showed a clear IFNg signature, with CXCL10 being one of the top ABMR classifier genes. 16 In a rat model of acute antibodymediated endothelial injury, among several chemokines and chemokine receptors, CXCL10 was, by far, the most upregulated chemokine (119-fold), a result that also supports our findings. 17 Our multivariate linear regression analysis of the association of Banff scores with urinary biomarker levels revealed that, among microvascular inflammatory lesions, the peritubular capillaritis score but not the glomerulitis score seemed independently and significantly associated with the urinary chemokine level (Table 3).…”
Section: Discussionsupporting
confidence: 88%
“…Molecular markers have the potential to aid in refining the diagnosis and prognosis of renal allograft outcome. Loupy et al 16 recently showed that adding the molecular microscope strategy to a conventional analysis of biopsy samples from patients with ABMR significantly improved prognostication with regard to the risk of subsequent allograft loss. Interestingly, CXCL10 mRNA was one of the top ABMR classifier genes.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there is considerable heterogeneity among published studies with regard to how the molecular phenotype has been assessed and applied as a potential diagnostic and/or predictive tool 46. Over the last decade, transplant biopsies, blood, and urine have been studied comprehensively, primarily using transcriptomics, and have led to novel insights into the molecular phenotypes of organ transplants 47, 48, 49, 50, 51, 52, 53. Current ongoing studies—for example, the INTERCOM studies 47, 48—are assessing a molecular microscope approach in real time for examining kidney allograft biopsies and comparing the gene expression classifiers and diagnosis to the current gold standard histopathology.…”
Section: Prospects For Adopting Molecular Pathology In Renal Allografmentioning
confidence: 99%
“…Renal biopsy tissue can also be used for unbiased approaches such as microarray analyses, which may yield diagnostic molecular signatures (213,(369)(370)(371)(372)(373)(374). This ''molecular microscope'' has been shown to improve the diagnosis of rejection but also to reflect molecular alterations in fibrosis (375)(376)(377)(378).…”
Section: Diagnosis Of Renal Fibrosismentioning
confidence: 99%